2021
DOI: 10.1002/rrq.410
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Within‐ and Cross‐Language Relations Among Language, Preliteracy Skills, and Word Reading in Bilingual Learners: Evidence From the Science of Reading

Abstract: Research has shown that language and literacy skills in a first language (L1) are related to performance in a second language (L2) and that these relations are reciprocal. However, cross‐linguistic skills related to word reading are influenced by numerous factors. These include linguistic factors such as the specific language and literacy skills being examined and the languages being compared. They also include societal/contextual factors, such as the linguistic and educational contexts where learners reside. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 142 publications
1
15
0
Order By: Relevance
“…Another clear direction for future research is to include multiple languages, as well as individuals who speak multiple languages, to assess similarities and differences of RAN as a predictor reading ability (Gottardo et al, 2021). In the past, other authors had suggested that RAN is a better predictor in more transparent languages (see Georgiou et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Another clear direction for future research is to include multiple languages, as well as individuals who speak multiple languages, to assess similarities and differences of RAN as a predictor reading ability (Gottardo et al, 2021). In the past, other authors had suggested that RAN is a better predictor in more transparent languages (see Georgiou et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, learning to read in Spanish is not the same as learning to read in English, and understanding how children in Spanish-speaking countries develop their reading skills is important to ensure their mastery of early reading components to allow them then to devote their mental processes to understanding what they read. We hypothesize that there are possible differences in how and when the essential components of reading predict reading comprehension in Spanish compared to English (see also Florit & Cain, 2011;Gottardo et al, 2021;Seymour et al, 2003).…”
Section: Purpose Of Studymentioning
confidence: 99%
“…The predictive relationship between early reading skills such as phonological awareness (the ability to manipulate sound sequences e.g., say cat without the /k/ sound ) and reading accuracy is well‐established for monolingual children (e.g., Hulme & Snowling, 2013), and the growing body of research on bilingual children shows similar predictive patterns for bilingual populations (see e.g. Gottardo et al, 2021 for a recent review). Bilingual early reading research, however, is yet to fully capture the intricate characteristics of different types of bilinguals, especially for children who grow up in dense diaspora communities.…”
Section: The Role Of Phonology In Early Reading Developmentmentioning
confidence: 99%